The effectiveness of effective microorganisms in treating wastewater - Navanitharuban, Batumalai (2017)
This paper present the studies on the effectiveness of using effective microorganisms (EM) in treating wastewater by using molasses, honey and sugar as a solution on activating it. It also determined the removal efficiency and also compared the three types of EM solutions in removing pollutants from the wastewater sample. EM is a group of 250 bacteria mainly consist of three types of microbes that are yeast, lactic acid, and photosynthetic bacteria. It is widely used for the purpose of wastewater treatment and purification that contribute to the significant of reduction on the water quality parameters such as chemical oxygen demand (COD), pH value, biological oxygen demand (BOD), total suspended solids, turbidity, ammoniacal nitrogen, oil & grease, and heavy metals. The EM was produced accurately and was activated by using sugar, honey and molasses. The sample of the wastewater was collected from morning market of Taman Tas, Kuantan. The data showed by using activated EM with molasses, the percentage of BOD removal was 43.64%, COD removal was 84.01%, TSS removal was 55.17%, zinc removal was 72.5%, and nickel removal was 90.28%. Furthermore, the data also showed by using activated EM with honey, the percentage of BOD removal was 38.37%, COD removal was 81.95%, TSS removal was 62.07%, zinc removal was 67.5%, and nickel removal was 84.72%. On the other hand, it also showed by using activated EM with sugar, the percentage of BOD removal was 30.93%, COD removal was 78.73%, TSS removal was 72.41%, zinc removal was 62.5%, and nickel removal was 81.9%. Moreover, all of the activated effective microorganisms removed 100% the oil & grease, and ammoniacal nitrogen from the wastewater. The results showed that the removal efficiency of the three types of activated effective microorganisms were successful. The study indicated that the treatment process using EM was effective.